Phenomenological Analysis of Civic Engagement Education Transformation in Indonesia's Post-Covid-19 Democracy System - Khairiyah, Nanda (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The transformation of civic engagement education in Indonesia's democratic system post-COVID-19 is of particular concern, given the significant changes in mindsets, behaviors, and societal demands. Therefore, the purpose of this study is to describe the experiences and perceptions of young people involved in youth organizations regarding the changes occurring in civic engagement education post-COVID-19. This study uses a qualitative method with a phenomenological approach. Subjects included academics, students, government officials, community activists or NGOs, and the general public involved in or affected by civic engagement education. Data collection techniques included interviews, participant observation, and other supporting instruments. Data analysis was conducted inductively. Interview transcripts and observation results were analyzed in depth to identify emerging themes and patterns. The results of this study indicate that although civic engagement education in youth organizations has been quite successful in informing students about the importance of political participation, feelings of skepticism and apathy towards politics continue to hinder youth from actively participating. This poses a challenge for future civic engagement education, which must create a stronger connection between the knowledge taught and the social and political realities faced by young people. Furthermore, there is a need to further integrate civic engagement education into young people's daily experiences, not just the theory learned in classes or seminars. Civic engagement education has undergone a transformation post-COVID-19, yet many young people feel disconnected from Indonesia's democratic process.